Overexpression of BiP in tobacco alleviates endoplasmic reticulum stress. - Leborgne-Castel, N (1999)
To study the role of the lumenal binding protein (BiP) in the transport and secretion of proteins, we have produced plants with altered BiP levels. Transgenic plants overexpressing BiP showed dramatically increased BiP mRNA levels but only a modest increase in BiP protein levels. The presence of degradation products in BiP overproducers suggests a regulatory mechanism that increases protein turnover when BiP is abundant. Antisense inhibition of BiP synthesis was not successful, demonstrating that even a minor reduction in the basal BiP level is deleterious to cell viability. Overexpression of BiP leads to downregulation of the basal transcript levels of endogenous BiP genes and greatly reduces the unfolded protein response. The data confirm that BiP transcription is regulated via a feedback mechanism that involves monitoring of BiP protein levels. To test BiP activity in vivo, we designed a functional assay, using the secretory protein alpha-amylase and a cytosolic enzyme as a control for cell viability. During tunicamycin treatment, an overall reduction of alpha-amylase synthesis was observed when compared with the cytosolic marker. We show that the tunicamycin effect is due to the depletion of BiP in the endoplasmic reticulum because coexpressed BiP alone is able to restore efficient alpha-amylase synthesis. This is a novel assay to monitor BiP activity in promoting secretory protein synthesis in vivo.